THE RELATION OF MENTAL WORKLOAD AND STRESS MANAGEMENT ON TECHNICIAN’S JOB STRESS OF PT. X BRANCH SEMARANG - Ajeng Dyah Pradipta; Ekawati Ekawati; Siswi Jayanti (Jurnal Kesehatan Masyarakat, 2019)
Job stress is the inability of an individual or worker to resolve work demands and the discrepancy between the individual's condition and the environment. Factors that can affect job stress include work factors such as the task system, job volume, job responsibilities, job environment or as a result of being unable to adapt someone to others at work, and cultural factors of workplace organization. Car repair workshop technicians experience work stress due to high job demands. Job stress can be overcome by applying appropriate stress management including time management, expressing feelings, positive thinking, recreation, sports and sharing stories. Work in an official workshop requires high concentration due to complex job. The purpose of this study is to analyze the relationship between mental workload and stress management with the job stress of PT. X Branch Semarang. The research method used is quantitative with cross sectional study. Samples selected using a total sampling of 30 people. With NASA-TLX, GHQ-12 and the questionnaire are the research instruments. Based on statistical tests of the relationship with the Spearman Rank (p value 0.105) there is no relationship between mental workload with job stress and the results of the statistical relationship test with the Spearman Rank (p value 0.002) there is a relationship between stress management and work stress. Researchers give advice to companies to create job stress counseling units and job stress socialization to technicians to minimize job stress.